The Role of AI in Diagnosing Student Learning Needs: Solutions for More Inclusive Education - Wayahdi, M. Rhifky; Zaki, Mohammed (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
This research explores the role of Artificial Intelligence (AI) in diagnosing students' learning needs and creating a more inclusive educational environment. Employing a mixed-methods approach, data were collected through surveys, interviews, and analysis of existing AI systems. The results indicate that AI has significant potential in identifying patterns in students' academic performance and learning preferences. Notably, 75% of students reported that AI aids their learning process, with average scores increasing from 70 to 85 after implementing AI systems. Additionally, 70% of students experienced enhanced engagement in their learning activities. However, challenges such as data privacy and algorithmic bias must be addressed. The study recommends collaboration among educators, technology developers, and researchers to create AI systems that are responsive to diverse learning needs. With the right approach, AI can serve as a powerful tool to improve learning outcomes and foster a more equitable and inclusive educational environment for all students. This research highlights the transformative potential of AI in education while emphasizing the importance of ethical considerations and stakeholder involvement in its implementation.